Superfluid transition in quasi-two-dimensional disordered dipolar Fermi gases - Pinchenkova, Victoria Y.; Matveenko, Sergey I.; Yudson, Vladimir I.; Shlyapnikov, Georgy V. (Comptes Rendus. Physique)
We investigate the effect of weak disorder on the superfluid properties of two-component quasi-two-dimensional dipolar Fermi gases. The dipole-dipole interaction amplitude is momentum dependent, which violates the Anderson theorem claiming that the weak disorder has practically no influence on the superfluid transition temperature in the weakly interacting regime. We find that for dipolar fermions the transition temperature in this regime can be strongly increased by the disorder like in the purely two-dimensional case. However, the effect becomes smaller with increasing the intercomponent fermion-fermion interaction, and in the strongly interacting regime the superfluid transition temperature in the weak disorder becomes very close to that in the absence of disorder.